2023
DOI: 10.3390/su15054462
|View full text |Cite
|
Sign up to set email alerts
|

Do Sustainable Consumers Have Sustainable Behaviors? An Empirical Study to Understand the Purchase of Food Products

Abstract: Sustainability and the circular economy (CE) are issues of increasing interest to governments, investors, industry, and civil society; for this reason, the implementation of a business model for circularity and/or sustainability is becoming crucial for achieving and maintaining a competitive advantage for various organizations. In this context, consumers play a crucial role in reducing the environmental impact of business processes through their choices and behaviors. “Sustainable consumption” is a growing glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…In contrast, impulsive or unplanned purchases can lead to considerable environmental harm. This underlines the significant environmental impact associated with consumer behavior (Gallo et al, 2023).…”
Section: Introductionmentioning
confidence: 85%
“…In contrast, impulsive or unplanned purchases can lead to considerable environmental harm. This underlines the significant environmental impact associated with consumer behavior (Gallo et al, 2023).…”
Section: Introductionmentioning
confidence: 85%
“…Jones et al (2016) studied proenvironmental indicators such as water, land, and energy use, as well as greenhouse gas emissions. Gallo et al (2023) found that the growing consumer concern about the environmental impact of water and energy usage in food production emphasizes the need for information regarding product labeling and marketing strategies. Rani et al (2019) investigated water use efficiency and proposed key measures for producers to adopt sustainable practices and meet the growing consumer demand for water-friendly products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Por ejemplo, De-Magistris y López-Galán (2021), segmentaron su muestra en tres grupos según la percepción, las actitudes hacia la miel y diferentes estilos de vida, encontrando un grupo más concienciado por el medioambiente, la nutrición y la salud, otro más centrado en el precio y otro intermedio. Annunziata y Mariani (2018) también clasificaron su muestra en diferentes segmentos de consumidores con diferentes percepciones de sostenibilidad, alimentos orgánicos y locales; y Gallo et al (2023) propusieron tres grupos de consumidores, unos más concienciados con la sostenibilidad y el medio am-biente y que están más dispuestos a adoptar elecciones de compra sostenibles, otros indiferentes a las cuestiones medioambientales y, por último, algunos consumidores con una atención mínima a la sostenibilidad.…”
Section: Análisis Clústerunclassified
“…Diversos estudios han analizado la relación entre el comportamiento sostenible en la vida diaria y la preferencia de los consumidores por los alimentos locales (Bimbo et al, 2020); al mismo tiempo se ha demostrado que los consumidores consideran los alimentos orgánicos y locales como alternativas sostenibles (Annunziata y Mariani, 2018). Los consumidores más concienciados con el medioambiente son los que trasladan esta inquietud al comportamiento de compra y eligen productos más sostenibles (Gallo et al, 2023). Por ello en este trabajo se ha recogido información sobre los hábitos de comportamiento sostenibles de los consumidores y se han puesto en relación con la percepción hacia la miel local.…”
Section: Introductionunclassified